The CDK Inhibitor SIAMESE Targets Both CDKA;1 and CDKB1 Complexes to Establish Endoreplication in Trichomes. Issue 1 (21st July 2020) - Wang, Kai; Ndathe, Ruth W.; Kumar, Narender; Zeringue, Elizabeth A.; Kato, Naohiro; Larkin, John C.
Abstract: The cyclin-dependent kinase inhibitor SIAMESE (SIM) targets both CDKA;1 and CDKB1 complexes, leading to establishment of endoreplication, and SIM interacts with the cyclin CYCA2;3 via SIM motif A. Abstract: Endoreplication, also known as endoreduplication, is a modified cell cycle in which DNA is replicated without subsequent cell division. Endoreplication plays important roles in both normal plant development and in stress responses. The SIAMESE ( SIM ) gene of Arabidopsis ( Arabidopsis thaliana ) encodes a cyclin-dependent kinase (CDK) inhibitor that plays a central role in establishing endoreplication, and is the founding member of the SIAMESE - RELATED ( SMR ) family of plant-specific CDK inhibitor genes. However, there has been conflicting evidence regarding which specific cyclin/CDK complexes are inhibited by SIM in vivo. In this work, we use genetic evidence to show that SIM likely inhibits both CDKA;1- and CDKB1-containing CDK complexes in vivo, thus promoting endoreplication in developing Arabidopsis trichomes. We also show that SIM interacts with CYCA2;3, a binding partner of CDKB1;1, via SIM motif A, which we previously identified as a CDK-binding motif. By contrast, SIM motif C, which has been indicated as a cyclin binding motif in other contexts, appears to be relatively unimportant for interaction between SIM and CYCA2;3. Together with earlier results, our work suggests that SIM and other SMRs likely have a multivalent interaction with CYC/CDK complexes.